Projecting stratocumulus transitions on the albedo-cloud fraction relationship reveals linearity of albedo to droplet concentrations - Goren,T; Feingold,G; Gryspeerdt,E; Kazil,J; Kretzschmar,J; Jia,H; Quaas,J (Geophysical Research Letters, 2022)
Satellite images show solid marine stratocumulus cloud decks (Sc) that break up over the remote oceans. The Sc breakup is initiated by precipitation and is accompanied by a strong reduction in the cloud radiative effect. Aerosol has been shown to delay the Sc breakup by postponing the onset of precipitation, however its climatic effect is uncertain. Here we introduce a new approach that allows us to re-cast currently observed cloud cover and albedo to their counterfactual cleaner world, enabling the first estimate of the radiative effect due to delayed cloud breakup. Using simple radiative approximation, the radiative forcing with respect to pre-industrial times due to delayed Sc breakup is −0.39 W m−2. The radiative effect changes nearly linearly with aerosol due to the droplet concentration control on the cloud cover, suggesting a potentially accelerated warming if the current trend of reduction in aerosol emissions continues.